Dynamic analysis and validation of a multi-body floating wind turbine using the moving frame method - Grindheim, Ole-Martin; Xing, Yihan; Impelluso, Thomas (Frontiers in Mechanical Engineering, 2023)
This research applies the moving frame method (MFM) to the multi-body dynamic analysis of an OC3 phase IV spar buoy with the NREL 5MW turbine. Further, it verifies previous results obtained through numerical comparisons with commercial software. The long-term goal is to lay the foundation for leveraging the MFM to create a self-contained software system for future analyses that can incorporate effects that are more sophisticated, when commercial codes fall short. In this first evidentiary phase, this project treats the floating turbine as a three-bodied system consisting of the platform (platform + tower), nacelle and rotor (hub + blades). Then the paper presents the MFM in a tutorial style-in the context of this problem's resolution. The paper supplements the multi-body dynamic equations of motion obtained through the MFM with simplified and reduced hydrodynamic, aerodynamic and mooring loads to simulate the translational and rotational response of the floating turbine under various load conditions. The results closely approximate those found in previous work and, in the process, demonstrates MFM's analytical advantage. Current results capture the coupled responses in all degrees of freedom and gyroscopic effects occurring when the platform pitches with the spinning rotor. The project thus provides an accurate model for the dynamics of the turbine and opens the door to inserting correct advanced hydrodynamics to validate the model further. The work presents simulations for the different load cases through a 3D web page using WebGL and the ThreeJS library. Users may download all software to verify the results. An undergraduate student conducted the work alone, demonstrating the ease of implementation of the MFM.